1994
DOI: 10.1177/112067219400400109
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Pars Plana Vitrectomy and Silicone Oil for Complications of Diabetic Retinopathy

Abstract: Pars plana vitrectomy (PPV) with silicone oil implantation (SOI) was performed for advanced proliferative diabetic retinopathy (PDR) in 110 eyes of 98 diabetic patients. In 77 eyes (70%) it was a primary SOI as part of the initial operation; in 33 eyes (30%) it was a secondary SOI in reoperations. Indications for SOI were traction retinal detachment of the posterior pole, combined traction and rhegmatogenous detachment, vitreous haemorrhage with florid vascularised fibrous proliferations, and recurrent vitreou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In general, silicone oil removal should be attempted after 3 months to prevent the formation of secondary glaucoma or of cataract. 2 Intraocular silicone oil can migrate into the subconjunctival space and orbit through an Ahmed glaucoma valve. 3 Migration of silicone oil into the upper eyelid from the vitreous cavity after traumatic retinal detachment surgery is very rare and few cases have been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In general, silicone oil removal should be attempted after 3 months to prevent the formation of secondary glaucoma or of cataract. 2 Intraocular silicone oil can migrate into the subconjunctival space and orbit through an Ahmed glaucoma valve. 3 Migration of silicone oil into the upper eyelid from the vitreous cavity after traumatic retinal detachment surgery is very rare and few cases have been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually reserved for complex cases of retinal detachments [2] and proliferative diabetic retinopathy associated with tractional retinal detachment [3,4]. These agents are also primarily injected in eyes with severe trauma to stabilize the retina and inhibit the proliferative activity period that follows such complex cases [5].…”
Section: Introductionmentioning
confidence: 98%
“…5). Evidence of improving visual results during the last 20 years following vitrectomy has been shown in studies reported by Blankenship, 60 Thompson,[61][62][63][64] Sigurdsson, 65 Flynn, 66 Nakazawa 67 , Karel, 68 Harbour, Pendergast, 70 La Heij, 71 Yamamoto, 72 Amino, 73 Lewis, 74 Lahey, 75 Treumer, 76 Schrey, 77 and Diolaiuti. 78 However, a restriction in driving field has recently been reported in over two-thirds of patients in a small series of patients by Barsam 79 .…”
Section: Advances In the Management Of Diabetic Retinopathymentioning
confidence: 92%